Factors Affecting Performance of Framework Contract In Public Sector: A Case of Muhimbili University of Health and Allied Sciences - Getrude John Danieli; Doris Raphael (Rescollacom (Research Collaborations Community), 2026)
Framework contracts have become prevalent in public procurement. This is in an attempt to increase efficiency, reduce administrative fees, and increase timely delivery of commodities and services. However, the usage of framework contracts by Muhimbili University of Health and Allied Sciences (MUHAS) is slowed down by challenges related to the management of the contracts, capacity, and the performance of the supplier. This research offers empirical evidence of factors contributing to the performance of Framework Contracts. It examined the effect of Procurement Management Practices (PMP), Supplier Relationship Management (SRM), and Monitoring & Evaluation Systems (MES) on a mixed methods research design of a case study in collaboration with 65 procurement officers, contract managers, and suppliers. On describing the quantitative data through analysis using regression analysis, it was found that PMP (B = 0.779, p < 0.001), SRM (B = 0.429, p < 0.001), and MES (B = 0.189, p = 0.019) are highly predictive of factors resulting in good performance of the contract (R² = 0.849). This research also concludes in agreement through triangulation of the results indicating effective procurement, trust, and monitoring & evaluation contributing towards enhanced efficiency, compliance, & delivery of services. It also concludes that upgrading the processes of purchase, collaboration, & monitoring & evaluation of purchase as highly essential.